Konstitusi Ekonomi Menghadapi Masyarakat Ekonomi ASeAn (MeA) Tahun 2015 - Agustine, Oly Viana (Jurnal Konstitusi, 2014)
Constitutional economics is the main out line of the state indetermining the policy direction in the preparation, implementation and protection of the country’s economy and citizens. Thought contained in the constitutionin economics will be a guide in the country’s economic development and economic policy formation. Importance of economics in the constitution, would be a zone defense in them iddle of the development of the more advanced economies of the developed and developing countries in preparation for the implementation of the ASEAN Economic Community (AEC) by 2015 MEA conceptis formed by a single market in Southeast Asia. MEA it self aim stoin crease competition and improve the quality of ASEAN citizens to be able tobe competitive with people outside ASEAN. In addition to the MEA expected to attractin ward investment in ASEAN so as to provide increased economic and social welfare of ASEAN. With the MEA provides an easier alternative path way in which a country is able to sell the products of both goods and services easily.